Online language learning using virtual classrooms: an analysis of teacher perceptions. Issue 5 (4th July 2022) - Manegre, Marni; Sabiri, Kashif Ali
Abstract: This study explains the emergence of virtual classrooms as an online language learning (OLL) instruction method. There is clarification of how virtual classroom systems operate, followed by a discussion of the benefits of learning in these environments. Private corporations are capitalizing on OLL and generating an estimated global gross income of 86 billion USD. While these corporations likely create quality educational materials that are of interest to the student, the materials presented in these platforms are currently not regulated, and, while some companies follow CEFR guidelines, there is no guarantee whether they meet the standards of education boards in the public sector. We surveyed 35 OLL teachers who teach English in virtual classrooms for their perceptions and opinions in working in this environment. Not only did we discover that over 50 percent of the online teachers who participated have also been students, which is of interest because they have both teaching and learning experience in virtual classrooms, but also that these teachers generally believe that teaching English online in virtual classrooms creates a positive teaching environment for both the teacher and the student. The participants generally feel they get to know the students better in virtual classrooms than in other teaching environments. The teachers also perceive that students in virtual classrooms learn at the same rate or faster than in traditional classrooms and that, not only would they like to see more subjects offered online, but they also generally believe that online learning in virtual classrooms may be an alternative learning method to replace traditional classroom learning and home-schooling in most subjects. Continued attention should be paid to the educational opportunities in virtual classrooms, not just for OLL, but for the emergence of other curricula as well.